SLOW TOURISM AS AN ALTERNATIVE TO MASS TOURISM: A LITERATURE REVIEW AND CASE STUDIES - Novaković, Đurđina (The Business of Tourism, 2024)
Increasing concern about the negative impacts of mass tourism on the environment, culture, and local communities has sparked interest in alternative forms of tourism. Slow tourism represents one of these forms, focused on slow, mindful, high-quality, and sustainable travel that emphasizes a deeper connection with local culture, communities, and nature. The concept of “slow” thinking encourages tourists to step away from their daily tasks. This concept is increasingly attracting travelers who are free from the pressures of mass tourism and who seek authentic experiences and more meaningful interactions with destinations. This paper provides a comprehensive review of the literature on slow tourism, exploring its concept, evolution, and current scope. In addition to theoretical insights, the paper includes case studies that illustrate the practical aspects of slow tourism. Through analysis, the key characteristics and potentials of slow tourism as a sustainable alternative to mass tourism are identified, with the aim of providing new insights into its application and impact. Also, this analysis contributes to deepening the knowledge of new trends in tourism and furthering the author’s research on the development of this phenomenon.